Preparing raw clinical data for publication: guidance for journal editors, authors, and peer reviewers. (28th January 2010) - Hrynaszkiewicz, Iain; Norton, Melissa L; Vickers, Andrew J; Altman, Douglas G
Abstract : Many peer reviewed journals now require authors to be prepared to share their raw, unprocessed data with other scientists or state the availability of raw data in published articles, but little information on how such data should be prepared for sharing has emerged. Iain Hrynaszkiewicz and colleagues propose a minimum standard for de-identifying datasets to ensure patient privacy when sharing clinical research data